Phase formation and texture evolution in 316L-CuCrZr multi-material structures fabricated by laser powder bed fusion - Antonios Baganis; Florencia Malamud; Jan Čapek; Fedor F. Klimashin; Efthymios Polatidis; Matteo Busi; Miroslav Šmíd; Michal Jambor; Johann Michler; Markus Strobl; Christian Leinenbach (Materials & Design)
Steel-copper multi-material structures produced via Additive Manufacturing pose challenges in laser co-processing and microstructural control. This work employs neutron imaging, Electron Backscatter Diffraction (EBSD), and Energy Dispersive Spectroscopy (EDS) mapping to characterize 316L-CuCrZr Functionally Graded Structures (FGS) fabricated via Laser Powder Bed Fusion. Polarization Contrast Neutron Imaging (PNI) tracks ferrite formation in 316L-CuCrZr premixtures, while Neutron Bragg Edge Imaging (BEI) examines the texture evolution of the 316L-CuCrZr mixtures. PNI and EBSD phase mapping confirm ferrite formation in mixtures exceeding 50 wt% CuCrZr, appearing as spherical particles that locally increase hardness, as shown by nano-indentation mapping. The ferrite fraction peaks between 70–80 wt% CuCrZr. Simultaneously, BEI and EBSD Inverse Pole Figures (IPF) mapping reveal a crystallographic texture transition and grain refinement for mixtures containing more than 50 wt% CuCrZr. Microstructure analysis shows cracks in 10–40 wt% CuCrZr mixtures, while compositions with more than 50 wt% CuCrZr result in crack-free structures. EDS mapping and thermodynamic modeling suggest ferrite formation mechanisms in both liquid and solid states. This study highlights how FGS engineering enables precise control over crack formation, microstructure, and crystallographic texture in steel-copper multi-material structures.